SYNTHESIS, CHARACTERIZATIONS AND CORROSION INHIBITION PERFORMANCE OF TRANSITION METAL (II) COMPLEXES DERIVED FROM; ACETOPHENONE AND 2,4-DINITROPHENYLHYDRAZINE - Muhammad, Halliru; Lawan, Ishaq Yahaya; Ahmad, Aminu; Yahaya, Sunusi; Mahmoud, Khadija Aminu (FUDMA Journal of Sciences, 2026)
This study reports the synthesis, characterization, and corrosion inhibition performance of a hydrazone ligand derived from acetophenone and 2,4-dinitrophenylhydrazine, along with its Zn(II), Cu(II), Ni(II), Co(II), and Mn(II) complexes. The ligand and complexes were synthesized via condensation and metal-chelation reactions, and characterized using melting point determination, solubility tests, FTIR spectroscopy, conductivity measurements, and magnetic susceptibility analysis. Corrosion inhibition on mild steel was evaluated using the weight-loss method in 0.1 M HCl at varying concentrations (0.2–0.6 g/L) and temperatures (303–323 K). Results confirmed successful formation of the ligand (67.5% yield) and complexes (60.37–75.24% yield). The ligand melted at 120°C, while complexes decomposed between 160–175°C. Color changes from yellow (ligand) to pale yellow [Co(II)], brown [Cu(II)], yellow [Ni(II), Zn(II)], and black [Mn(II)] confirmed complexation. All compounds were soluble in polar solvents but insoluble in non-polar media. Conductivity measurements (3.57–8.47 Ω⁻¹cm²mol⁻¹) confirmed non-electrolytic behavior with coordinated chloride ions. Magnetic susceptibility data revealed high-spin octahedral geometries for Co(II) (5.01 B.M.), Ni(II) (2.80 B.M.), Mn(II) (7.00 B.M.), and distorted octahedral for Cu(II) (2.10 B.M.), while Zn(II) was diamagnetic. FTIR analysis confirmed coordination through azomethine nitrogen (C=N shift from 1618 cm⁻¹ to 1566–1600 cm⁻¹) and N–H groups, with new M–N bands at 732–899 cm⁻¹. Corrosion inhibition efficiency increased with concentration for all inhibitors. At 0.6 g/L and 303 K, efficiency followed: Zn(II) (85.19%) > Cu(II) (75.18%) > Ni(II) (68.83%) > Co(II) ≈ Mn(II) (67.13%) > Ligand (66.37%), with corrosion rates significantly reduced compared to the blank (249.22 mmy⁻¹).